ANALISIS TINGKAT PENDAPATAN USAHATANI JAGUNG PIPILAN DI KABUPATEN SERANG PROVINSI BANTEN - Dian Anggraeni (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
Corn (Zea mays) is one of the strategic commodities in Indonesian economy, because it is the second carbohydrate-producing food after rice. This study aims to (1) know the cost of corn farming (2) to know the income of corn farming, (3) to know the feasibility of corn pipeline farm in Serang regency of Banten province. The method used in this research is survey. Method of determining sample by multi stage random sampling with total sample counted 41 farmers who plant corn pipilan. Data were analyzed by tabulation and using cost formula, farm income and R / C ratio. The results showed that 1). The average cost of corn farming is Rp 5,762,211.00 per hectare per planting season, 2). Average amount of corn farm income income Rp 10,668,564.00 per hectare per planting season, 3). R-C ratio of corn farming by 2.85. Thus, corn chin farming is feasible to be developed in Serang District.